Warfarin-induced isolated spontaneous subarachnoid hemorrhage: Rare case report. (December 2022) - Hassan, Mohamed Sheikh; Bakir, Ahmet; Adam, Bakar Ali; Sidow, Nor Osman; Ibrahim, Abdiwahid Ahmed; Abdi, Ishak Ahmed; Waberi, Mohamud Mire
Abstract: Introduction and importance: Subarachnoid hemorrhage (SAH) is mostly associated with head trauma. Non-traumatic subarachnoid hemorrhage is mostly due to vascular abnormalities: either hemorrhage from ruptured aneurysm or bleeding from arteriovenous malformation. Aneurysmal hemorrhage is the biggest cause in non-traumatic cases. Warfarin is associated with cerebral intraparenchymal hemorrhage, but it is rarely associated with SAH. Case presentation: Here, we report the case of a 45-year-old male patient who was admitted to the neurology ward of our hospital due to acute ischemic stroke. The patient was treated with a vitamin K antagonist (warfarin). However, on the third day, his condition deteriorated (his GCS regressed from 11/15 to 5/15). His pupils were anisocoric. Brain CT showed extensive subarachnoid hemorrhage without intraparenchymal involvement. Cerebral magnetic resonance angiography ruled out aneurysmal rupture. The patient was intubated and transferred to the intensive care unit. Due to his poor condition, neurosurgical intervention could not be done. The patient was managed conservatively, but the patient passed away 4 days later in the intensive care unit. Clinical discussion: Non-traumatic SAH is mostly caused by aneurysmal rupture. Warfarin increases the risk of intracranial hemorrhage and mostly causes intraparenchymal hemorrhage. Isolated warfarin-related SAH without parenchymal involvement is a rare event. Here we present a young male patient with an isolated warfarin-induced SAH. Conclusion: Warfarin is rarely associated with isolated subarachnoid hemorrhage. This case highlights a young male patient with spontaneous SAH after warfarin therapy for acute ischemic stroke. Aneurysmal rupture and trauma should be excluded before a diagnosis of warfarin-induced SAH is made. Highlights: Non-traumatic subarachnoid hemorrhage (SAH) is mostly caused by aneurysmal rupture. Warfarin increases the risk of intracranial hemorrhage and mostly causes intraparenchymal hemorrhage. Isolated warfarin-related SAH without parenchymal involvement is a rare event. Here we present a young male patient with isolated SAH due to warfarin treatment for acute ischemic stroke.